The spectralities reader : ghosts and haunting in contemporary cultural theory - Blanco, María del Pilar (Bloomsbury, 2013)
The Spectralities Reader is the first volume to collect the rich scholarship produced in the wake of the “spectral turn” of the early 1990s, which saw ghosts and haunting conjured as compelling analytical and methodological tools across the humanities and social sciences. Surveying the past twenty years from an interdisciplinary and cross-cultural perspective, the Reader displays the wide range of concerns spectrality, in its diverse elaborations, has been called upon to elucidate. The disjunctions produced by globalization, the ungraspable quality of modern media, the convolutions of subject formation (in terms of gender, race, and sexuality), the elusiveness of spaces and places, and the lingering presences and absences of memory and history have all been reconceived by way of the spectral. A primer for the wide readership engaged with cultural interpretations of ghosts and haunting that go beyond the confines of the fictional and supernatural, The Spectralities Reader includes twenty-five groundbreaking texts by prominent contemporary thinkers, from Jacques Derrida and Gayatri Spivak to Avery Gordon and Arjun Appadurai, as well as a general introduction and six section introductions by the editors.